Reading the Rewriting of National History Through Slavoj Žižek’s Approach - Ismail Ismail; Michael Silvester Mitchel Vinco (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study examines the reasons behind the omission of the history of sexual violence against Chinese women during the May 1998 Tragedy from Indonesian historiography. The study aims to trace how state ideology operates to exclude women’s bodily experiences from the official narrative. By employing Slavoj Žižek’s concepts of “the real” and “disavowal,” this study analyzes the absence of this issue in textbooks, educational policies, and public discourse. The research employs qualitative methods, specifically critical discourse analysis and a literature review of reports from the National Commission on Violence Against Women (Komnas Perempuan), Human Rights Watch, and academic studies. The findings reveal that Indonesian historiography is not neutral but shaped by nationalist fantasies that obscure collective wounds. The erasure of sexual violence is not merely an oversight but a political strategy to maintain the state’s image of stability. Therefore, historical writing that acknowledges victims is a crucial step toward narrative justice and social reconciliation.